2014
DOI: 10.1016/j.jsat.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary, randomized trial of aerobic exercise for alcohol dependence

Abstract: Interventions targeting physical activity may be valuable as an adjunct to alcohol treatment, but have been relative untested. In the current study, alcohol dependent, physically sedentary patients were randomized to: a 12-week moderate-intensity, group aerobic exercise intervention (AE; n = 25) or a brief advice to exercise intervention (BA-E; n=23). Results showed that individuals in AE reported significantly fewer drinking and heavy drinking days, relative to BA-E during treatment. Furthermore adherence to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
131
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(145 citation statements)
references
References 70 publications
(77 reference statements)
8
131
2
3
Order By: Relevance
“…This is supported by other studies where self-reported levels of PA in individuals with AUD approached or exceeded current averages for U.S. adults (R. A. Brown et al, 2014;Kendzor et al, 2008;Read et al, 2001). The fact that more than half of the participants in this study rated their level of fitness as "below average" or "poor" may also be further proof of the inconsistencies previously reported in accurately reporting PA levels and the intensity of this activity (Prince et al, 2008).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This is supported by other studies where self-reported levels of PA in individuals with AUD approached or exceeded current averages for U.S. adults (R. A. Brown et al, 2014;Kendzor et al, 2008;Read et al, 2001). The fact that more than half of the participants in this study rated their level of fitness as "below average" or "poor" may also be further proof of the inconsistencies previously reported in accurately reporting PA levels and the intensity of this activity (Prince et al, 2008).…”
Section: Discussionsupporting
confidence: 84%
“…There is growing interest in examining novel methods of primary and adjunct treatment for individuals with AUD, such as the impact of exercise training (Brown et al, 2014;Sari et al, 2013). To date, only a handful of studies (Abrantes et al, 2011;Read et al, 2001) have examined the attitudes and preferences of these individuals towards engaging in exercise training as a part of alcohol treatment out-patient programs.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies used aerobic exercise as the intervention, five studies used a combination of aerobic exercise, strength training and/or calisthenics15 55–58 and three studies used yoga/stretching 16 51 58. Most of the included studies (N=17) were supervised, either by a physical therapist or qualified exercise trainer; however, three studies involved a mixture of supervised and unsupervised exercise 16 55 59. Seventeen studies included an ‘active’ control intervention; for the long-term studies, this generally consisted of CBT, group counselling and/or pharmacotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Although still preliminary, existing studies demonstrate that physical activity might promote mental and physical health in persons with alcohol use disorder [2][3][4][5]. For example, review findings in persons with alcohol use disorder [4] indicate that physical activity might reduce drinking episodes and craving, while improving psychological outcomes like depression, anxiety and sleep quality and increasing physical fitness.…”
mentioning
confidence: 99%
“…There is a continuing debate about the amount (e.g., frequency, intensity, duration) of physical activity needed for the mental and physical health benefits in persons with alcohol use disorder [3,5]. Understanding the barriers and facilitators of participation in physical activity in alcohol use disorder is an essential first step in order to devise effective physical activity interventions.…”
mentioning
confidence: 99%